Altruism or social motives? evidence from online charitable giving in China. Issue 4 (3rd April 2022) - Chen, Xi; Song, Danyang; Shou, Yongyi; Pan, Yin
ABSTRACT: Despite the rapid development of online charitable giving (OCG), there are few empirical studies on the motivations of OCG. This study examines two typical types of motivations (i.e., altruism and social motives). We build a model by combining the elaboration likelihood model (ELM) of persuasion with social influence theory. Using a dataset of 13, 119 projects from Weibo Charity, a leading OCG platform in China, we find that the primary motivation of OCG comes from social motives rather than altruism. This study contributes to the relevant literature and provides practical implications for OCG project sponsors and platform managers.